2005
DOI: 10.1074/jbc.m507913200
|View full text |Cite
|
Sign up to set email alerts
|

RAC1 Inhibition Targets Amyloid Precursor Protein Processing by γ-Secretase and Decreases Aβ Production in Vitro and in Vivo

Abstract: ␤-Amyloid peptides (A␤) that form the senile plaques of Alzheimer disease consist mainly of 40-and 42-amino acid (A␤ 40 and A␤ 42) peptides generated from the cleavage of the amyloid precursor protein (APP). Generation of A␤ involves ␤-secretase and ␥-secretase activities and is regulated by membrane trafficking of the proteins involved in A␤ production. Here we describe a new small molecule, EHT 1864, which blocks the Rac1 signaling pathways. In vitro, EHT 1864 blocks A␤ 40 and A␤ 42 production but does not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 56 publications
0
60
0
Order By: Relevance
“…In Fragile X syndrome, the most common hereditary form of mental retardation, lack of Fragile X mental retardation protein (FMRP) induced an overactivation of RAC1 in the mouse brain, indicating that regulation of RAC1 may provide a functional link among deficient neuronal morphology, aberrant synaptic plasticity, and cognition impairment in this disease (31). Interestingly, in Alzheimer disease it has been found that RAC1 inhibition targets amyloid precursor protein processing by ␥-secretase and decreases A␤ production in vitro and in vivo (32). But RAC1 is not only involved in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fragile X syndrome, the most common hereditary form of mental retardation, lack of Fragile X mental retardation protein (FMRP) induced an overactivation of RAC1 in the mouse brain, indicating that regulation of RAC1 may provide a functional link among deficient neuronal morphology, aberrant synaptic plasticity, and cognition impairment in this disease (31). Interestingly, in Alzheimer disease it has been found that RAC1 inhibition targets amyloid precursor protein processing by ␥-secretase and decreases A␤ production in vitro and in vivo (32). But RAC1 is not only involved in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…-To investigate the implication of the canonical pathway of NF-B in the effects mediated by RAC1 Q61L , we used a dominant-negative mutant of IB␣ (IB␣ S32A/S36A ) in which Ser 32 and Ser 36 residues had been changed to Ala to block their phosphorylation and, consequently, their degradation. IB␣ S32A/S36A produced a dose-dependent inhibition of NF-B by RAC1 Q61L (Fig.…”
Section: Ib Is Implicated In Nrf2 and Nf-b-p65/p50 Activation By Rac1mentioning
confidence: 99%
“…[53] Another study identified EHT1864 (3)asaRac1 inhibitor,which effectively reduces Ab peptide levels in models of Alzheimers diesease in vitro (Figure 3a). [54] Further investigation of the mode of action led to the postulate that the compound tightly binds Rac1 with low nanomolar affinity (dissociation constant K d = 40 nm). Compound 3 acts through an oncompetitive mechanism, as observed for compound 2,which induces nucleotide release upon binding to Rac1.…”
Section: Interference With Nucleotide Bindingmentioning
confidence: 99%
“…67 Therefore, we hypothesized that electrotransfection could lead to actin remodeling and enhance macropinocytosis through activation of Cdc42 and Rac1. To test this hypothesis, we performed experiments with two pharmacological inhibitors, ML141 68 and EHT1864, 69 that targeted Cdc42 and Rac1, respectively. We chose these inhibitors because they are potent, selective, and most importantly reversible, which allowed us to observe the inhibitory effects without permanently interfering with cell signaling.…”
Section: Dna Uptake By Electrotransfection-induced Macropinocytosis Imentioning
confidence: 99%